The Design Concepts of "Shanashel", and its Effect on Functional and Environmental Performance - Saba Jabar Niema (Iraqi Journal of Architecture and Planning, 2009)
The design concepts of uaditional architecture have had greet potentiality throughtime for all social and environmental needs of the place and its inhabitance.And the idea of analyzing their contents and meaning to understand their effects inarchitecture on it both sides (theory and practice), in order to adapt their beneficial parametersfor modem architecture is so important for environmental design.This research concems with one of the design concepts of the traditional houses in theold fabric of the city which is the (Shanashel), and discuses their geometrical configuration,formal look, and material effect to show its functional and environmental performance(climate and acoustics). And has emphasized the later, as the facades acts as screens whichattenuate sounds due to banier theory and have good influence on acoustical environmentthrough diffusion and diffraction. In order to have some design parameters for architecturaldesign and research process within the modern look.